EXPERIMENT STUDY ON SURFACE QUALITY AND TOOL WEAR OF AL-SI ALLOY ZL114A BASED ON TURNING - WANG FuLin; LU XueYun; SUN XingZuo; WU YongWen (Jixie qiangdu)
Machined surface quality of Al-Si alloy aviation structural part affects its service performance. The cutting parameters have a strong correlation with the formation of surface quality, and surface quality can be improved by adjusting the cutting parameters. Single factor method was used to test the turning of ZL114A Al-Si alloy. To explore the influence law ofcutting parameters and tool nose radius on the surface quality and cutting performance of the workpieces, surface roughness, surface residual stress, surface morphology and tool wear of the specimen were observed and analyzed with cutting force and cutting temperature. The results show that the surface roughness of ZL114A Al-Si alloy is most sensitive to the change of turning depth. The machined surface residual stress is compressive stress, which is most sensitive to the change of tool nose radius. There are obvious tool marks on the surface of the workpiece after turning, accompanied by the appearance of pear ditch. The change of spindle speed has the greatest influence on tool wear.